Public-legal and private-legal regulation of entrepreneurial activity in the Republic of Kazakhstan - Nurmagambetov, Anet; Nurmagambetov, Amanzhol; Amandykova, Saule; Khassenov, Muslim; Nurmagambetova, Saule (Opción, 2019)
The purpose of the scientific article is to describe the problem of legal support of the balance of public-legal and private-legal regulation in the Republic of Kazakhstan in conditions of the market economy via formal-logical, historical-legal and systemic-analytical research methods. As a result, a competitive legal system attracts more business and investment under its jurisdiction, contributes to the implementation of bold and advanced ideas. In conclusion, the Entrepreneurial Code should become a guarantor of ensuring the balance of public and private interests in carrying out entrepreneurial activity by establishing at the normative level generally binding rules of conduct (prescriptions).